2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472288
|View full text |Cite
|
Sign up to set email alerts
|

Grab-n-Pull: An optimization framework for fairness-achieving networks

Abstract: In this paper, we present an optimization framework for designing precoding (a.k.a. beamforming) signals that are instrumental in achieving a fair user performance through the networks. The precoding design problem in such scenarios can typically be formulated as a non-convex max-min fractional quadratic program. Using a penalized version of the original design problem, we derive a simplified quadratic reformulation of the problem in terms of the signal (to be designed). Each iteration of the proposed design f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…To minimize w H Rw, we can equivalently maximize w H (−R)w. For total power constraint, this optimization problem can be solved efficiently using power-method [11]. The unimodular signal design can be handled by using powermethod like iterations introduced in [12].…”
Section: A Optimization W R T Wmentioning
confidence: 99%
See 4 more Smart Citations
“…To minimize w H Rw, we can equivalently maximize w H (−R)w. For total power constraint, this optimization problem can be solved efficiently using power-method [11]. The unimodular signal design can be handled by using powermethod like iterations introduced in [12].…”
Section: A Optimization W R T Wmentioning
confidence: 99%
“…It can be shown that the power constraint in (3) will be satisfied with equality, so we have w 2 = P . Following [11], the SINR expression can be written as…”
Section: System Model and Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations